Adipokinetic effect of corpora cardiaca extract in Valanga nigricornis (Burm.) - Lee, C. W.; Tan, C. H. (Elsevier, 1983)
1. The effect of injection of corpora cardiaca (CC) extract on haemolymph lipid concentration of V. nigricornis was studied. 2. The CC extract caused a marked increase in the haemolymph lipid, which attained a peak at about 1 1/2 hr after injection. At longer intervals of up to 4 hr, this response was markedly diminished. 3. The results were considered in relation to the natural habit of the insect; it is suggested that the adipokinetic effect probably represents an adaptive mechanism to non-flight physiological conditions like starvation.